Beneficiation of High‐Phosphorus Siderite Ore by Acid Leaching and Alkaline Oxide Reinforced Carbothermic Reduction‐Magnetic Separation Process. Issue 6 (29th December 2016) - Lv, Chao; Wen, Shuming; Yang, Kun; Bai, Shaojun
Abstract : In this study, the beneficiation of high‐phosphorus siderite ore by acid leaching dephosphorization, alkaline oxide reinforced carbothermic reduction and magnetic separation is investigated. X‐ray diffraction (XRD), scanning electron microscopy (SEM), and energy‐dispersive analysis (EDS) are employed to characterize the samples. The results indicate that the phosphorous mainly exists as fluorapatite and can be removed effectively by sulfuric acid leaching. The dephosphorization rate is 90.41% under proper conditions. Iron grain size in reductive ore without alkaline oxide additive (performed at 1000 °C for 150 min with 20% dosage of reductant coal) is tiny, and the fayalite is abundant. Moreover, the iron grain is closely associated with slag. With 12% dosage of alkaline oxide additive (Na2 CO3 :CaO = 1:1), the reduction of siderite is reinforced. The iron particle size in reduced ore is coarse and the diffraction intensity of metallic iron increases obviously. The reinforcing affect is mainly caused by an increase of the reducing reaction activity of FeO. After the grinding and magnetic separation process, an iron concentrate with 70.83% Fe and 0.05% P is obtained, which can be served as raw material for ironmaking. Abstract : This paper provides a method for beneficiation of high‐phosphorus siderite ore. A combined metallurgy process is developed, which includes dephosphorization using H2 SO4 leaching at low concentration, reinforces carbothermic reduction with alkaline oxide additives (Na2 CO3 and CaO) and magnetic separation process. An iron concentrate has a high metallic iron content and a low content of harmful impurities, which can be used as a raw material for iron‐making.